Exploring the liver fibrosis induced by deltamethrin exposure in quails and elucidating the protective mechanism of resveratrol - Siyu Li; Xiaoyan Zheng; Xiaoya Zhang; Hongxiang Yu; Bing Han; Yueying Lv; Yan Liu; Xiaoqiao Wang; Zhigang Zhang (Ecotoxicology and Environmental Safety, 2021)
Deltamethrin (DLM) is widely used in agriculture and the prevention of human insect-borne diseases. However, the molecular mechanism of DLM induced liver injury remains unclear to date. This study investigated the potential molecular mechanism that DLM induced liver fibrosis in quails. Japanese quails received resveratrol (500 mg/kg) daily with or without DLM (45 mg/kg) exposure for 12 weeks. Histopathology, transmission electron microscopy, biochemical indexes, TUNEL, quantitative real-time PCR, and western blot analysis were performed. DLM exposure induced hepatic steatosis, oxidative stress, inflammation, and apoptosis. Most importantly, the Nrf2/TGF-β1/Smad3 signaling pathway played an important role on DLM-induced liver fibrosis in quails. Interestingly, the addition of resveratrol, an Nrf2 activator, alleviates oxidative stress and inflammation response by activating Nrf2, thereby inhibits the liver fibrosis induced by DLM in quails. Collectively, these findings demonstrate that chronic exposure to DLM induces oxidative stress via the Nrf2 expression inhibition and apoptosis, and then results in liver fibrosis in quails by the activation of NF-κB/TNF-α and TGF-β1/Smad3 signaling pathway.